Investigation of the mechanisms and sensitivity of wellbore breathing effects during drilling in deepwater shallow formations. (1st February 2023) - Huang, Honglin; Li, Jun; Gao, Reyu; Zhang, Geng; Yang, Hongwei; Chen, Wang; Luo, Ming; Li, Wentuo
Abstract: Wellbore breathing effect (WBE) occurs during drilling in deepwater shallow formations (DSFs), but its background is different from the three mechanisms mentioned in the present literatures (radial elastic expansion in deep wells, mud expansion in high-temperature wells, and mud loss and backflow in fractured formations); therefore, proper explanation has not been done. To provide a persuasive proof, we consider the unique characteristics of DSF, which are highly porous and permeable, easily deformed, and have undeveloped fracture systems, and explore the mechanism of this WBE in conjunction with the phenomenon of WBE occurring in shallow formations when drilling deepwater wells in the South China Sea. Based on the fluid–solid coupling theory of Bingham fluids in porous elastic media, a new model was developed to simulate and describe the new WBE. The influences of the formation parameters (FPs), mud properties (MPs), and differential pressure (DP) on the WBE were analyzed. The results prove that the WBE in the process of drilling in DSFs involves a transient permeability induced wellbore breathing effect (PIWBE). FP and DP are two significant contributors to PIWBE. A formation with a low elastic modulus, low Poisson's ratio, and high porosity and permeability will produce a more intense PIWBE. Simultaneously, an increase in DP promotes the intensity of the PIWBE. The influence of MPs on the PIWBE was relatively weak. The strength of the PIWBE can be effectively reduced by optimizing the solid particle size, optimizing the MP (increasing viscosity and yield force and reducing density), adding a filtrate reducer, and adopting the MPD technology. Highlights: A new permeability-induced mechanism is proposed to explain the wellbore breathing effect that occurs during drilling in deepwater shallow formations. A new model of fluid-solid coupling was developed to simulate and analyze the permeability-induced wellbore breathing effect. The effects of different factors on the permeability wellbore breathing effect are discussed.